Assessment of prevalence, knowledge of polycystic ovary syndrome and health-related practices among women in klang valley: A cross-sectional survey - Goh, Jia Ean; Farrukh, Muhammad Junaid; Keshavarzi, Fazlollah; Yap, Chuan Sheng; Saleem, Zikria; Salman, Muhammad; Ramatillah, Diana Laila; Goh, Khang Wen; Ming, Long Chiau (Frontiers in Endocrinology, 2022)
Background Polycystic ovary syndrome (PCOS) is a common metabolic and reproductive disorder affecting women of childbearing age. Its symptoms associated with androgen excess and menstrual abnormalities have great impact on the quality of life in women with PCOS. Data on the knowledge of PCOS and health-related practices among Malaysian women is scarce. This study aimed to determine the prevalence, knowledge and health-related practices of PCOS among women in Klang Valley, Malaysia. Method A descriptive cross-sectional study was conducted among women in Klang Valley, Malaysia using a self-administered questionnaire. Participants were conveniently recruited through online platforms. Questionnaire consisted of four sections. The knowledge scores ranged from 0-20 where < 10 was classified as poor knowledge. Health-related practices scores ranged from 10-50, with score <30 was classified as poor practice. Descriptive statistics was used to report demographic characteristics. Inferential statistics was used to report the differentiation, association, and correlations of the variables. Results A total of 410 respondents participated in this survey. The finding revealed that 43 (10.49%) respondents had medical diagnosis of PCOS, 11 (2.68%) were diagnosed with PCOS based on signs and symptoms, and 135 (32.93%) were suspected with PCOS. Nearly half of the respondents had poor knowledge (47.30%) and poor practice (47.60%) of PCOS. Also, 46 (11.22%) respondents reported abnormal scalp hair loss and 30 (7.32%) respondents had diabetes. Educational levels and PCOS history were significantly associated with PCOS knowledge. Respondents with healthcare related educational background demonstrated good knowledge (p<0.01). Majority of respondents (n= 328, 80%) were unable to control their diets on weekends. Married participants and aged between 40 to 45 women showed better practice of PCOS. Conclusion Nearly half of the respondents had poor knowledge and health-related practices towards PCOS. Women with suspected or diagnosed PCOS should seek immediate medical help as early diagnosis and treatment for PCOS are beneficial in improving their quality of life.